1996
DOI: 10.1093/jn/126.suppl_4.1201s
|View full text |Cite
|
Sign up to set email alerts
|

Oxidant-Antioxidant Status Alterations in Cancer Patients: Relationship to Tumor Progression

Abstract: A significant change of vitamin E and malondialdehyde plasma concentrations was reported in breast cancer patients. This change was unexpected because vitamin E was higher and malondialdehyde lower in cases than in controls, and the difference was more significant in young rather than older women. The first aim of this study was to determine whether these changes were associated only with breast cancer, or with hormone-related cancers, and/or cancers associated with nutritional risk factors or with all types o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
19
2

Year Published

1998
1998
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 17 publications
5
19
2
Order By: Relevance
“…The deleterious effects of lipoperoxides on survival appear to contradict the results of our previous [3][4][5] and present cross-sectionnal studies. Most studies relating to the possible role of lipoperoxides in breast cancer carcinogenesis have investigated the role of PUFA as a highly peroxidable substrate.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The deleterious effects of lipoperoxides on survival appear to contradict the results of our previous [3][4][5] and present cross-sectionnal studies. Most studies relating to the possible role of lipoperoxides in breast cancer carcinogenesis have investigated the role of PUFA as a highly peroxidable substrate.…”
Section: Discussioncontrasting
confidence: 99%
“…The deleterious effects of vitamin E appear to contradict the results of previous studies [3][4][5] and also what one would expect in relation to the role of vitamin E, an inhibitor of PUFA peroxidation. The relationship between plasma and tissue vitamin E levels and breast cancer is inconsistent.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…Both electrontransfer physical effects (catalytic formation and then rotational/vibrational dissipation of the triplet excited state of the carotenoid) and chemical reactions (consuming the beta-carotene or oxidizing the beta-carotene) are involved in inactivating peroxy and alkoxy radical species, and superoxide anion. Radical addition to carotenoids from lipid peroxyl radicals can be induced by the effect on lipid membranes of singlet oxygen, nitrogen dioxide, or thiyl radical (derived from the interaction of NO2 with glutathione) (23,29). Carotenoids differ in their propensity to react through these various pathways with various radicals and in different in vitro test systems.…”
Section: Mechanisms Of Actionmentioning
confidence: 99%
“…Oxidative stress in the target tissue has been suggested to play an important role in carcinogenic process. Thus, Se may act as an antitumoural agent although more studies are needed to investigate the actual role of antioxidants and their possible relationships with trace elements alterations in the pathogenesis of breast cancer (Bock et al, 1991;Gerber et al, 1996). Furthermore, it has been shown that Se supplementation decreases the COX-2 protein and PGE-2 levels in colorectal cancer cells.…”
mentioning
confidence: 99%